Unveiling metabolic changes in stored rice seeds: A metabolomics approach - Poornima, S; Vigneshwari, R; Manonmani, V; Boominathan, P; Renuka, R (Plant Science Today, 2025)
Rice is a vital staple crop that not only served as a primary food source but also contributed significantly to the national economy. Its propagation through seeds was therefore crucial for ensuring sustainable agricultural productivity. However, seed viability declined over time due to physiological and biochemical changes during storage, leading to deterioration and reduced quality. Understanding these metabolic changes was essential for preserving seed longevity. Metabolomics emerged as a robust analytical approach for profiling a wide range of rice seed metabolites and identifying biomarkers linked to seed ageing. Techniques like mass spectrometry (MS) and nuclear magnetic resonance (NMR) allowed for high-resolution, comprehensive analysis. Metabolomics enabled early detection of seed ageing with high accuracy and supported strategies that extended rice seed viability. This enhanced seed quality management and reduced post-harvest losses effectively. This review highlighted the metabolite composition of rice seeds, factors influencing changes during storage, key metabolomics methodologies and their applications in improving seed quality, longevity and future breeding programs.